Climate changes in North Africa and the possibilities of adapting to it with ecosystem approaches - Vovk Korže, Ana; Štefane, Manuela (Journal for Geography, 2016)
The article deals with geographical characteristics of North Africa with the focus on climate changes which are reflected in particular by the increase in the average temperatures and decrease of precipitation. These conditions have a direct impact on the reduction of agriculture and on the changes in land use. Further on, this has a direct impact on the way of life of people. The use of ecosystem technologies (imitation of nature) can be an easy and effective way to contain water in the region. Water also has a significant role in survival. Therefore, the use of ecoremediation (imitation of nature) in North Africa could mitigate climate changes.